THE ANALYSIS OF SCIENCE PROCESSING IN BIOLOGY OF X GRADE STUDENTS OF SENIOR HIGH SCHOOL â€œYâ€ IN PONOROGO REGENCY - Dewi, Nurul Kusuma; Ardhi, Muh. Waskito (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
Science processing skills (SPS) is a psychomotor ability in 2013 curriculum. The implementation of SPS can be done well in the planning or in the learning process. This research aimed to analyze X grade studentsâ€™ potentials of SPS in biology in senior high school â€œYâ€, Ponorogo regency. This research used descriptive qualitative research. The data in this research were collected from non-test way using observation and documentation. The learning process was analyzed using the instrument of SPS evaluation in eight aspects 1) formulating the hypothesis, 2) planning experiment, 3) conducting the experiment, 4) doing observation, 5) interpreting data, 6) predicting, 7) implementing the concept, and 8) communicating. These aspects have four indicators. The analyzed learning process was in the material of Bryophyte and Pteridophytes. The analysis of data was in descriptive quantitative. The results of the analysis were aspect 3) was 35.29%, aspect 4) was 23.54%, aspect 5) was 11.76%, aspect 6) was 11.76%, and aspect 8) was 17.65%. Based on the analysis, it can be concluded that X grade studentsâ€™ science processing skills in Senior High School â€œYâ€ Ponorogo regency have not been optimally used and in the low category. It is suggested that there should be a planning and designing of practicum in the learning process.